Gold labelling of a green fluorescent protein (GFP)-tag inside cells using recombinant nanobodies conjugated to 2.4 nm thiolate-coated gold nanoparticles. Issue 24 (19th October 2021) - Groysbeck, Nadja; Donzeau, Mariel; Stoessel, Audrey; Haeberle, Anne-Marie; Ory, Stéphane; Spehner, Danièle; Schultz, Patrick; Ersen, Ovidiu; Bahri, Mounib; Ihiawakrim, Dris; Zuber, Guy
Abstract : A specific and non-covalent approach is reported to associate the targeting ability of nanobodies with the detectability of 2.4 nm gold nanoparticles for immunolabelling of cellular effectors using light and high-resolution electron microscopy. Abstract : Advances in microscopy technology have prompted efforts to improve the reagents required to recognize specific molecules within the intracellular environment. For high-resolution electron microscopy, conjugation of selective binders originating from the immune response arsenal to gold nanoparticles (AuNPs) as contrasting agents is the method of choice to obtain labeling tools. However, conjugation of the minimal sized 15 kDa nanobody (Nb) to AuNPs remains challenging in comparison to the conjugation of 150 kDa IgG to AuNPs. Herein, effective Nb-AuNP assemblies are built using the selective and almost irreversible non-covalent associations between two peptide sequences deriving from a p53 heterotetramer domain variant. The 15 kDa GFP-binding Nb is fused to one dimerizing motif to obtain a recombinant Nb dimer with improved avidity for GFP while the other complementing dimerizing motif is equipped with thiols and grafted to a 2.4 nm substituted thiobenzoate-coordinated AuNP via thiolate exchange. After pegylation, the modified AuNPs are able to non-covalently anchor Nb dimers and the subsequent complexes demonstrate the ability to form immunogold label GFP-protein fusions within various subcellular locations. These tools open an avenue for precise localization of targets at high resolution by electron microscopy.